PEMANFAATAN KULIT BUAH NAGA MERAH DAN PENAMBAHAN UBI JALAR UNGU PADA PEMBUATAN SIRUP - Qori Oktragangga; Netti Herawati; Rahmayuni Rahmayuni2 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to determine the effected ofred dragon fruit peel and addition of purple sweet potato of to the quality of syrup. This research used Complete Randomized Design (CRD) with four treatments and four replications which followed by Duncan’s New Multiple RangeTest(DNMRT) at level 5%.The treatments in this research wereNJ1(red dragon fruit peel extracts 90% : purple sweet potato pulp 10%), NJ2(red dragon fruit peel extracts 80% :purple sweet potato pulp20%), NJ3 (red dragon fruit peel extracts 70%:purple sweet potato pulp30%) andNJ4(red dragon fruit peel extracts 60% :purple sweet potato pulp 40%). The resultsof this reserch showed that the utilization of red dragon fruit peel and addition ofsweet potato significantly effected on pH, sucrose, viscosity, and sensory value (colour, flavour, taste, viscous, and overall acceptability).  The best treatment syrup was NJ4(dragon fruit peel extracts 60% :sweet potato pulp 40%) was pH 4.93, sucrose 65.91%, viscosity 128.20 cP, and descriptives test of NJ4 are the colour was purple,the flavour wasred dragon fruit peel and purple sweet potato,the taste wasred dragon fruit peel and purple sweet potato, the viscous was rather liquid, and hedonic testwas preferred by panelist. Keywords : Syrup,dragon fruit peel, sweet potato pulp